2002
DOI: 10.1118/1.1470207
|View full text |Cite
|
Sign up to set email alerts
|

Surface area overestimation within three‐dimensional digital images and its consequence for skeletal dosimetry

Abstract: The most recent methods for trabecular bone dosimetry are based on Monte Carlo transport simulations within three-dimensional (3D) images of real human bone samples. Nuclear magnetic resonance and micro-computed tomography have been commonly used as imaging tools for studying trabecular microstructure. In order to evaluate the accuracy of these techniques for radiation dosimetry, a previous study was conducted that showed an overestimate in the absorbed fraction of energy for low-energy electrons emitted withi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 39 publications
1
20
0
Order By: Relevance
“…The lower image resolution in z direction ͑CT slice thickness͒ generates a slightly stair-stepped surface of the external features of the older phantoms and their internal organs, with a corresponding overestimate of their sur-face area. 28 Previous studies from both Jones 29 and Zankl, 30 however, indicate that these voxelized organ surfaces do not significantly influence dosimetry results for photon irradiations. The rather unsmooth surfaces near the abdomen of the 9-month phantom are thought to be due to breathing artifacts introduced during the CT scan.…”
Section: Resultsmentioning
confidence: 95%
“…The lower image resolution in z direction ͑CT slice thickness͒ generates a slightly stair-stepped surface of the external features of the older phantoms and their internal organs, with a corresponding overestimate of their sur-face area. 28 Previous studies from both Jones 29 and Zankl, 30 however, indicate that these voxelized organ surfaces do not significantly influence dosimetry results for photon irradiations. The rather unsmooth surfaces near the abdomen of the 9-month phantom are thought to be due to breathing artifacts introduced during the CT scan.…”
Section: Resultsmentioning
confidence: 95%
“…However, because of the jagged representation of the boundary between voxels, this segmentation does not preserve the surface area of the interface between the 2 media. This voxel effect has consequences for dosimetric assessment using Monte Carlo transport and is especially important for low-energy electrons (35). At a 6-mm voxel size, the effect is pronounced for electron energies below 20 keV (e.g., for electrons emitted by 3 H or 125 I).…”
Section: Micro-ct Model Of Carbon Scaffoldmentioning
confidence: 99%
“…It is well known that the process of discretizing an analytically defined surface inevitably leads to errors because a continuous surface is truncated into a finite number of bins [19][20][21]. Table 1 describes results obtained from the discretization of a pore using different voxel sizes.…”
Section: Isolated Spherical Porementioning
confidence: 98%
“…Peter et al [19] found that discretization of actual phantom geometry yielded inaccurate simulations compared to those obtained with analytical phantoms in their Monte-Carlo simulations for nuclear biomedical application. Rajon et al [20,21] emphasized that image voxelization overestimates the surface area of the bone-marrow interface, thereby leading to errors in cross-dose to bone as high as 25% for some low-energy beta emitters. They also found that the overestimation cannot be reduced through reduction of the voxel size (e.g., improved image resolution).…”
Section: Introductionmentioning
confidence: 99%